54. tGLI1 IS AN ACTIONABLE THERAPEUTIC TARGET IN BREAST CANCER BRAIN METASTASES. (4th August 2020) - Doheny, Daniel; Sirkisoon, Sherona; Rimkus, Tadas; Zhu, Dongqin; Aguayo, Noah; Anguelov, Marlyn; Manore, Sara; Regua, Angelina; Thomas, Alexandra; Henson-Masters, Adrianna; Strowd, Roy; Lo, Hui-Wen
Abstract: Breast cancer is the second leading cause of brain metastases in women; patients with breast cancer brain metastasis (BCBM) survive an average of 6–18 months following diagnosis. Cancer stem cells are thought to be one of the driving forces behind distant metastasis, treatment resistance, and late-stage recurrence. The hedgehog-smoothened pathway has been identified as an important mediator of breast cancer stem cells (BCSC); however, FDA-approved therapies targeting smoothened have demonstrated limited clinical efficacy in breast cancer. Despite advances made in understanding BCSC, it is still challenging to effectively target BCSC underscoring the need to identify and inhibit novel mediators of BCSC for treating BCBM patients. Our laboratory recently reported that truncated glioma-associated oncogene homolog 1 (tGLI1) promotes preferential metastasis to the brain in breast cancer by activating BCSC and astrocytes in the tumor microenvironment (Oncogene 39:64–78, 2020). tGLI1 was discovered in our laboratory as an alternatively spliced GLI1 that functions as a tumor-specific gain-of-function transcription factor and terminal effector of the hedgehog pathway. We found that tGLI1 knockdown abrogated BCBM, providing the rationale to therapeutically target tGLI1. Cell-based chemical screens followed by validations demonstrated that ketoconazole, an FDA-approved azole antifungal, specifically inhibits tGLI1 leading to suppression of BCSC in vitro and BCBM in vivo. Based on these data, we opened a window-of-opportunity study in patients with BCBM to determine if ketoconazole penetrates the blood-brain barrier (BBB) and alters tGLI1 signaling in humans (NCT03796273). Preliminary sample analysis has confirmed tGLI1 expression in collected BCBM samples. To help identify more effective tGLI1 inhibitors, we screened 63 azole compounds for tGLI1-selectivity and identified four additional compounds as potential tGLI1 inhibitors. Animal studies were performed to compare the efficacy of these four compounds with ketoconazole in suppressing BCBM. Collectively, these data establish tGLI1 as an actionable target for BCBM.